Sustainable Revenue Strategies For Public Transport: A Case Study of PT LRT Jakarta’s Advertising Transformation - Fajar Handoko Dewantoro; Dikky Indrawan; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: PT LRT Jakarta faces significant challenges in optimizing non-farebox revenue, particularly from advertising, which experienced a drastic 99.41% decline in 2022.Purpose: This study aims to analyze the root causes of these challenges and provide strategic recommendations to enhance advertising revenue.Design/methodology/approach: The research employs qualitative methods, integrating VRIO, PESTLE, and SWOT frameworks to evaluate internal resources, external environmental factors, and strategic opportunities.Findings/Result: The findings reveal that PT LRT Jakarta possesses strengths such as strategic advertising locations and advanced digital signage technology, yet it also faces weaknesses in equipment availability and operational inefficiencies. External opportunities include supportive government policies and economic growth, while threats such as regulatory constraints and cybersecurity risks Conclusion: By leveraging its strengths, addressing weaknesses, capitalizing on opportunities, and mitigating threats, PT LRT Jakarta can significantly enhance its non-farebox revenue. Proposed strategies include enhancing digital advertising infrastructure, forming strategic partnerships, and adopting environmentally friendly innovations. Originality/value (State of the art): This study contributes uniquely by integrating VRIO, PESTLE, and SWOT frameworks to devise actionable advertising strategies tailored for public transportation. The findings provide practical insights to help PT LRT Jakarta optimize non-farebox revenue. Keywords: Advertising strategy, non-farebox revenue, public transportation advertising, PT LRT Jakarta, strategic management